PENGARUH KUALITAS LAYANAN TERHADAP KEPUASAN PELANGGAN PADA HOTEL HORISON DI MAKASSAR - Kherayani Nur (Lembaga Penelitian, Publikasi dan Pengabdian pada Masyarakat (LP3M) Nobel Indonesia, 2015)
This study aims: to study and analyze the most dominant variable effect on customer satisfaction Hotel Horison Makassar. In this study used multiple regression analysis. The data used in this study was obtained from the Hotel Horison Makassar. The sample used in this study is the Hotel Horison Makassar customers as much as 96 people. Sample selection is done by using purposive sampling method. The results showed that: 1) the results of the analysis of partial test shows that the variable tangible (physical evidence) has a positive and significant impact on customer satisfaction at the Hotel Horison Makassar, 2) the results of the analysis of partial test shows that variable reliability (reliability) has a positive influence and significant impact on customer satisfaction at the Hotel Horison Makassar, 3) the results of analysis of partial test shows that the variable responsiveness (responsiveness) has a positive and significant impact on customer satisfaction at the Hotel Horison Makassar, 4) the results of analysis of partial test shows that the variable assurance ( guarantees) has positive and significant impact on customer satisfaction at the Hotel Horison Makassar, 5) the results of analysis of partial test shows that the variable empathy (attention) has a positive and significant impact on customer satisfaction at the Hotel Horison Makassar, and 6) the results of analysis of simultaneous test obtained that the variable quality of service in the form of reliability (reliability) is the most dominant variable effect on customer satisfaction at Horison Hotel in Makassar.